1.Преобразуйте в многочлен:

а)(f+6)²=

б)(2f-2)²=

в)(2e-5)(2e+5)=

г)(6e+3b)(6e-3b)=

2.Разложите на множители:

a)r²-36=

б)81w²-18wx+x²=

3.Выполните действия:

а)(c²-4f)(4f+c²)=

б)(u⁴-5u)²=

в)(u-g)²(u+g)²=

2

Ответы и объяснения

2013-05-14T16:44:11+00:00

1.a) (f+6)^2=f^2+12f+36

    b) (2f-2)^2=4f-8f+4

     c) (2e-5)(2e+5)=(4e^2-25)

     d) (6e+3b)(6e-3b)=(36e^2-9)

2. a) (r-6)(r+6)

     b) (9w-x)^2

 

Лучший Ответ!
2013-05-14T16:47:00+00:00

f^2+12f+36

4f^2-8f+4

4e^2-25

36e^2-9b^2

 

(r-6)(r+6)

(9w-x)

 

c^4-16f^2

u^8-10u^5-25u^2

(u^2-2ug+g^2)(u^2+2ug+g^2)=u^4+2u^3g+u^2g^2-2u^3g-4u^2g^2-2ug^3+g^2u^2+2ug^3+g^4= =u^4-2u^2g^2+g^4